2010
DOI: 10.1038/onc.2010.285
|View full text |Cite
|
Sign up to set email alerts
|

The BRG1 ATPase of chromatin remodeling complexes is involved in modulation of mesenchymal stem cell senescence through RB–P53 pathways

Abstract: We focused our attention on brahma-related gene 1 (BRG1), the ATPase subunit of the SWItch/Sucrose NonFermentable (SWI/SNF) chromatin remodeling complex, and analyzed its role in mesenchymal stem cell (MSC) biology. We hypothesized that deviation from the correct concentration of these proteins, which act at the highest level of gene regulation, may be deleterious for cells. We wanted to know what would happen if a cell had to cope with altered regulation of gene expression, either by upregulation or downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 66 publications
(94 reference statements)
3
31
0
Order By: Relevance
“…If senescence is inhibited, however, cells become prone to carcinogenesis. Previous studies have shown that overexpression of BRG1 may lead to cellular senescence (28). Additionally, BRG1 is required for formation of senescence-associated heterochromatin foci (SAHF) (20).…”
Section: Discussionmentioning
confidence: 99%
“…If senescence is inhibited, however, cells become prone to carcinogenesis. Previous studies have shown that overexpression of BRG1 may lead to cellular senescence (28). Additionally, BRG1 is required for formation of senescence-associated heterochromatin foci (SAHF) (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several laboratories have demonstrated that TERT forms complexes independent of the telomerase RNA hTERC (9,11,15). Specifically, we along with others have found that hTERT binds BRG1 and NS and that this complex regulates both gene transcription (11) and stem cell function in normal and malignant cells (15,39,40) in a manner independent of telomere maintenance. Here, we report that the levels of this complex are increased in mitotic cells but not in asynchronously cycling cells (41) and that suppressing each of the members of this complex arrests cells in mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, H2AX depletion suppressed the DDR-dependent senescence-associated growth arrest and IL-6 secretion, indicating that the activated DDR signalling during senescence has a functional role, mediated also by γH2AX presence. Supporting the idea that senescent PDDF are a signature of stable chromatin alterations, rather than classical DSBs, changes in chromatin organization are sufficient to induce senescence and are associated with increase in H2AX phosphorylation (104,105). Recently our group described for the first time the presence of PDDF in adult stem cells (106), thus extending the impact of this non-canonical H2AX role in senescence maintenance to undifferentiated cells.…”
Section: The Histone H2ax Non-canonical Rolesmentioning
confidence: 92%